Accurately reflecting uncertainty when using patient-level simulation models to extrapolate clinical trial data - Dakin, H; Leal, J; Briggs, A; Clarke, P; Holman, R; Gray, A (SAGE Publications, 2020)
Introduction: Patient-level simulation models facilitate extrapolation of clinical trial data while allowing for heterogeneity, prior history, and nonlinearity. However, combining different types of uncertainty around within-trial and extrapolated results remains challenging.